RUTF: Could This Alternative Therapy be The Answer For Severely Malnourished Children In LMICs? a Critical Meta-Analysis - Razan, Rafi Alfian; Widjaja, Nur Aisiyah; Shabrina, Farah Aisha; Ananda, Naoval Diza; Oktavian, Puguh (Universitas Airlangga, 2026)
Introduction: Childhood malnutrition in the under-5 age group represents a critical challenge to global health systems. Current WHO treatment protocols recommend standardized formula diet (F-100) following the stabilization period to facilitate catch-up growth. In recent years, Ready-to-Use Therapeutic Food (RUTF) has gained widespread adoption across low- and middle-income countries (LMIC) owing to its accessibility for community-level interventions. The established benchmark for appropriate weight gain in children between 6-60 months ranges from 5-10 g/kg/day. Objectives: The present investigation sought to evaluate the comparative effectiveness of RUTF versus F-100 in promoting weight gain among malnourished children. Methods: This investigation adhered to the 2020 PRISMA guidelines for systematic reviews and meta-analyses. Statistical analyses employed standard meta-analytic procedures with random effects modeling based on the classical DerSimonian–Laird approach, implemented in R version 4.4.1. Data from eight investigations involving 2084 participants were synthesized to evaluate the principal outcome of bodyweight increase. Results: Children receiving RUTF demonstrated significantly superior weight gain relative to those receiving F-100. RUTF administration resulted in an additional 2.96 g/kg/day weight gain compared to F-100 ([95% CI 1.82 to 4.16], p-value <0.001). Children managed with RUTF exhibited elevated rates of weight gain compared to F-100 recipients. Despite both interventions promoting weight increase, neither achieved the velocity necessary for adequate catch-up growth in LMIC children presenting with severe acute malnutrition (SAM). Conclusions: These findings emphasize the necessity for novel supplementation approaches to achieve optimal catch-up growth in children with SAM.